(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
When a woman with mullerian agenesis presents with blind or absent vagina, management options include surgical vaginoplasty or non surgical self dilatation. Vaginal dilation should be the first line management of mullerian agenesis. Because of the need for motivated, mature patients and long term dilatation and follow up, gynecologists usually go for surgical vaginoplasty. We tried a novel approach to nonsurgical dilation of vagina in the cases of mullerian agenesis. We injected normal saline into the potential space of vagina between urethra and rectum and applied digital pressure daily for 14-15 days. This procedure created a vaginal space which was to be further dilated by regular coitus and/ or vaginal dilators. We are presenting here a series of three cases of mullerian agenesis managed by non surgical vaginal dilatation, facilitated by prior saline injection and sustained digital pressure. Bangladesh J Obstet Gynaecol, 2021; Vol. 36(1): 65-68